Editorial - Editorial Committee, Guest (Austral Journal of Veterinary Sciences, 2023)
Working equids play a fundamental role in human society, strengthening the human livelihoods and improving the resilience capacity of communities through their contribution to economic, environmental, and social capital. Donkeys, horses and mules facilitate access to vital resources including water and health care. Furthermore, their use in traction, cargo and transportation can be regarded as a significant clean and renewable energy resource, providing a wider, systemic contribution to the sustainability of agroforestry-based economies in a wide variety of ecosystems, such as mountain regions.